Learning and collaboration technologies : 4th International Conference, LCT 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: 4th International Conference, LCT 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2017) - Unknown
No abstract available